DiffMan: An object-oriented MATLAB toolbox for solving differential equations on manifolds - Engø, Kenth; Marthinsen, Arne; Munthe-Kaas, Hans Z. (Applied numerical mathematics, 2001)
We describe an object-oriented MATLAB toolbox for solving differential equations on manifolds. The software reflects recent development within the area of geometric integration. Through the use of elements from differential geometry, in particular Lie groups and homogeneous spaces, coordinate free formulations of numerical integrators are developed. The strict mathematical definitions and results are well suited for implementation in an object-oriented language, and, due to its simplicity, the authors have chosen MATLAB as the working environment. The basic ideas of DiffMan are presented, along with particular examples that illustrate the working of and the theory behind the software package.